A QUALITATIVE STUDY OF OBSTACLES TO THE IMPLEMENTATION OF THE 4P MARKETING STRATEGY AT SUGI COFFEE HOUSE IN PALU CITY - Palawa, Muh. Riswandi; Ibrahim, Andi Indriani; Asri, Nilam Cahya; Padondan, Anita Clara; Mardiani, Dewi (Universitas Indo Global Mandiri Palembang, 2025)
Objective: This study aims to identify the obstacles faced by Sugi Coffee House in implementing the 4P marketing strategy, focusing on product, price, place, and promotion. It provides insights into how these factors affect the café’s market reach and overall performance. Design/Methods/Approach: Using a qualitative approach with descriptive analysis, data were collected through in-depth interviews with managers and direct observation. The study examines the real-world challenges faced by the café in a competitive environment in Palu City, Indonesia. Findings: The research identifies key obstacles in each of the 4P areas: in product, there are challenges with raw material storage due to limited cooling facilities; in price, an initial high price was adjusted to make it more affordable for a broader market; in place, limited parking space affects customer comfort; and in promotion, fierce competition from neighboring cafés is a significant barrier to attracting customers’ attention. Originality/Value: This study contributes to the literature on marketing strategies in the context of small and medium-sized enterprises (SMEs), especially in the food and beverage sector in Indonesia. It emphasizes the practical constraints faced by SMEs and offers insights into how the 4P strategy can be adapted to better address these challenges. Practical/Policy Implication: The study suggests that café owners should enhance storage facilities, improve parking arrangements, and explore more diverse promotional strategies, including paid ads. Additionally, policymakers could assist SMEs by providing support in marketing and operational improvements to ensure the sustainability of local businesses.